Reducing Packaging Defects in Wheat Flour Production Using Soft Systems Methodology - Edna Maryani; Pratama Jaya (Golden Ratio of Mapping Idea and Literature Format, 2026)
Product packaging quality plays a crucial role in maintaining product safety, reducing rework, and sustaining company competitiveness. This study aims to reduce defects in 25 kg wheat flour packaging at PT. XYZ by identifying dominant defect types and analyzing their root causes. A Soft Systems Methodology (SSM) approach—an interpretive, systems-based framework used to analyze complex, unstructured problem situations—was applied to structure the problem, develop conceptual models, and propose improvements. Based on production data, 653 packaging defects were recorded. The dominant defects were packaging leakage at the seams (51.60%) and damage during loading (36.29%), representing 87.89% of total defects. Root cause analysis using Pareto and fishbone diagrams identified human factors, improper methods, and material quality as the primary contributors. Improvement proposals include selecting higher-quality thread, optimizing operator working schedules, providing ergonomic support tools, establishing loading limits, and strengthening SOP implementation. The implementation of these improvements is expected to reduce rework levels, improve productivity, and enhance packaging reliability.